2000
DOI: 10.1074/jbc.m003135200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nuclear Localization Signal in Human DNA Topoisomerase I

Abstract: DNA topoisomerase (topo) I is a nuclear enzyme that plays an important role in DNA metabolism. Based on conserved nuclear targeting sequences, four classic nuclear localization signals (NLSs) have been proposed at the N terminus of human topo I, but studies with yeast have suggested that only one of them (amino acids (aa) 150 -156) is sufficient to direct the enzyme to the nucleus. In this study, we expressed human topo I fused to enhanced green fluorescent protein (EGFP) in mammalian cells and demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 45 publications
3
53
0
Order By: Relevance
“…In addition, the K117R mutant showed essentially the same CPT sensitivity as wildtype Topo1, in agreement with the fact that CPT binds to Topo1 near the active site of the C-terminal domain (Pommier et al, 1995;Stewart et al, 1998). Meanwhile, the N-terminal domain, containing four NLS sequences, is important for Topo1 to localize in the nucleus and functioning in vivo (Mo et al, 2000a;Stewart et al, 1996aStewart et al, ,b, 1997. The K117R and K153R Figure 4 DNA relaxation activities and CPT sensitivities of WT and K117R Topo1.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, the K117R mutant showed essentially the same CPT sensitivity as wildtype Topo1, in agreement with the fact that CPT binds to Topo1 near the active site of the C-terminal domain (Pommier et al, 1995;Stewart et al, 1998). Meanwhile, the N-terminal domain, containing four NLS sequences, is important for Topo1 to localize in the nucleus and functioning in vivo (Mo et al, 2000a;Stewart et al, 1996aStewart et al, ,b, 1997. The K117R and K153R Figure 4 DNA relaxation activities and CPT sensitivities of WT and K117R Topo1.…”
Section: Discussionsupporting
confidence: 56%
“…1) ) were emphasized as its NLS. Because the BD does not contain a classic NLS, the nuclear localization of GSK-3β seems to be not mediated by importin α (Mo et al, 2000;Takeda et al, 2000). We assumed that these two basic sequences are the part of PY-NLS.…”
mentioning
confidence: 99%
“…whether caspase-mediated cleavage of Top1 contributes to or results from Top1cc formation. Prior studies have shown that cleavage of Top1 to the 80-kDa form does not prevent its nuclear localization (38) and that 80-kDa Top1 retains its ability to form Top1cc in cells exposed to camptothecin (7). In vitro experiments have further demonstrated that truncated 68-kDa C-terminal recombinant Top1 is still catalytically active (37).…”
Section: Caspase-3-cleaved Top1 Is Preferentially Involved In the Apomentioning
confidence: 99%
“…Caspase-3 cleaves Top1 after aspartate residue 146 and generates an 80-kDa C-terminal fragment (Fig. 4A) that remains capable of forming Top1cc (7, 37) and still possesses one functional nuclear localization signal (38) (Fig. 4A).…”
Section: Top1 Induces Apoptotic Nuclear Fissionmentioning
confidence: 99%